Aktualisasi Teori Hukum Progresif dari Aspek Hukum Pidana: Peninjauan Restorative Justice - Az Zanubiya, Siti Syafa; Syahuri , Taufiqurrohman (Journal Evidence Of Law, 2024)
The idea of progressive law encourages the community to be responsive to making breakthroughs in practicing law in Indonesia. Not only shackled by positivistic and legal analytical thoughts. Law is not only driven by positive law and invitation regulations but law can move towards non-formal, this is an opportunity to run progressive law. To answer what has become a problem formulation in this study. This research uses a juridical-normative approach. Legal materials in this study are primary legal materials which include: 1945 Constitution of the Republic of Indonesia, Law Number 48 of 2009 concerning Judicial Power, as well as Police Regulation Number 8 of 2021 and Regulation of the Attorney General of the Republic of Indonesia Number. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. Therefore, it emphasizes the study of library materials and the disclosure of the meaning of a The data source used is secondary data, conducted through library research. In line with progressive law that does not survive if the situation causes decadence of a corrupt atmosphere and harms the community. It would be better if the restorative justice mechanism is injected into the criminal justice system first by identifying the case model.